Transcutaneous vagus nerve stimulation: a bibliometric study on current research hotspots and status - Fan, Shiyu; Yan, Long; Zhang, Junfeng; Sun, Yujia; Qian, Yulin; Wang, Meng; Yu, Tao (Frontiers in Neuroscience, 2024)
ABSTRACT BACKGROUND Transcutaneous Vagal Nerve Stimulation (tVNS) has been used as a promising noninvasive neuromodulation technique for the treatment of various systems.The aim of this study was to analyze the research hotspots and future directions of tVNS in the 21st century by using bibliometric methods. METHODS The study object was the literature related to tVNS from the Web of Science database from 2000 to May 2024. In order to measure and analyze the number of literature issuance, institutions, authors, countries, keywords, co-citations, and journals of publication, we used VOSviewer, Citespace, Bibliometrix R-package, and Scimago Graphica software. A narrative review of the current research content of tVNS was conducted to gain a better understanding of the current state of the field. RESULTS A total of 569 papers were included in the study. The results show that from 2000 to 2024, the number of publications shows an increasing trend year by year, involving a total of 326 research institutions. The United States, China, and Germany are the major research centers. The study identified 399 keywords, which roughly formed 11 natural clusters, revealing that the current hotspots of related research are mainly reflected in 3 areas: intervention efficacy on nervous system diseases, mechanism of action of tVNS, and stimulation mode of tVNS. The top 10 most cited references focus on research into the mechanism of action of tVNS. CONCLUSION The efficacy and safety of tVNS have been confirmed in previous studies, but a standardized tVNS treatment protocol has not yet been developed, and most clinical studies have small sample sizes and lack multicenter and multidisciplinary collaboration. Currently, tVNS is used in the treatment of neurological diseases, psychiatric diseases, cardiovascular diseases, and some autoimmune diseases. It is expected that future research in this field will continue to focus on the application of tVNS in central nervous system diseases and the exploration of related mechanisms, and at the same time, with the rise of non-invasive neuromodulation technology, the application of tVNS in other diseases also has great potential for development.